RoboCup 2011: robot soccer world cup xv - Rofer, Thomas (Lecture Notes in Computer Science, 2012)
This book includes the thoroughly refereed post-conference proceedings of the 15th Annual RoboCup International Symposium, held in Istanbul, Turkey, in July 2011. The 12 revised  papers and 32 poster presentation presented were carefully reviewed and selected from 97 submissions. The papers are orginazed on topical sections on robot hardware and software, perception and action, robotic cognition and learning, multi-robot systems, human-robot interaction, education and edutainment and applications.